National team biathletes` experiences of the menstrual cycle: "it`s something that needs to be heard" - Jørgensen, H.; Davenport, M. H.; Holt, N. L.; McHugh, T.-L. F. (BMJ Open Sport & Exercise Medicine, 2025)
Objectives To describe national team biathletes` experiences of their menstrual cycle (MC) while training and competing, and to identify factors to be considered in the development of policy and practice to support these athletes.